"Residential Surveillance at a Designated Residence": A Special Form of Pre-trial Detention in China's Criminal Procedure. Issue 127 (2nd January 2021) - Zhou, Zunyou
ABSTRACT: In China, 'residential surveillance at a designated residence, ' as provided by its current Criminal Procedure Law, is a special form of pre-trial detention designed allegedly as a non-custodial measure to reduce the rate of pre-trial custody. However, legal provisions concerning this measure tacitly allow suspects to be held incommunicado for up to six months without access to relatives and lawyers. The measure is also highly problematic in legal practice, because it often acts as a convenient tool for bypassing regular legal safeguards. 'Residential surveillance at a designated residence' is very similar to two other measures—' shuanggui ' and ' liuzhi '—with Chinese characteristics. The repressive detention measure stains China's struggle for the rule of law.